INITIAL DATA ON THE RELIABILITY AND VALIDITY OF THE DEPRESSION,ANXIETY, STRESS SCALE (DEPRESSION, ANXIETY, STRESS SCALE – DASS) - Leontieva, Lora (E-Journal VFU, 2024)
The beginning of a procedure for adaptation of the Depression, Anxiety, Stress Scale in Bulgarian is presented. Initial psychometric data reveal good reliability and validity. The methodology and the main theoretical concepts in the development of the scale are described. The results of the statistical analysis reveal a good construct and convergent validity and excellent internal consistency of both the individual subscales and the entire Scale. The T-test for independent samples shows that the scales for depression, anxiety, stress are sensitive to the measured characteristics in clinical and non-clinical samples, with the mean values significantly higher in a clinical sample.